Two‑stage optimization of Allura direct red dye removal by treated peanut hull waste - Torres Perez, Jonatan (2020)
In this work, a series of experimental studies on the adsorption of Allura direct red dye (R40) on an as-prepared adsorbent has been carried out. The adsorbent has been produced from the activation of peanut hulls with steam at approximately 850 °C. The current study has gone beyond isotherm modeling; for example, optimization has been carried out to minimize the mass of adsorbent used in order to achieve the most economically feasible setup for industrial applications. Additionally, aside from kinetic modeling, contact time optimization has also been conducted for an adsorption process consisting of a setup using batches of adsorbent with filtration between each stage known as a multistage process such a process can increase efficiency, decrease the amount of adsorbent used, and improve the economic feasibility of the process. It is shown that, with an adsorbent loading rate of 1 g/L, it is possible to achieve 99% removal of the dye if adequate contact time is provided. Depending on the removal percent required, it is possible to reduce the residence time by more than 75% via the optimized multistage batch adsorption process. Thus, the prepared adsorbent is very effective at removing the Allura dye, and as such, can be an environmentally friendly and low-cost adsorbent for wastewater treatment.